DEVELOPMENT OF PHYSIC LEARNING ANIMATION MEDIA USING ADOBE FLASH CS5 - Gere, Amirullah A.; Syukroyanti, Bq. Azmi; Prayogi, Saiful (Lensa : Jurnal Kependidikan Fisika, 2016)
This research aims to develop a medium of learning physics animation using Adobe Flash CS5 software on the subject of momentum and impulse. Testing the feasibility of learning through the media trial on 2 validator, ie material experts and design media. This study using ADDIE development model, namely Analysis, Design, Development, Implementation, Evaluation. This study only uses three stages, namely until the stage of development of animation media learning software designed using Adobe Flash CS5. Validation matter experts on media appearance and suitability of materials with the acquisition of a score of 3.6 that is rated "very valid." Validation specialist media design to display the main menu with the acquisition of a 3.7 score so classified as"very valid." Media planning and expert validation of the content of the material and the suitability of the animation with the acquisition of a score of 3.7 and is rated "very valid." Next to, the survey of 10 students 2nd semester of physics education by looking into the matter and the overall learning animation media with the acquisition of a score of 3.38 and is rated "very valid." Thus the media animation of learning developed worthy as a medium of learning physics subject of momentum and impulse.